European Jewry in the Age of Mercantilism, 1550-1750 - Israel, Jonathan, 1946- (Littman library of Jewish civilization (Series), 1998)
This survey history of Jewish life and culture in early modern Europe is the first to focus on the sixteenth and seventeenth centuries as a radically new phase in Jewish history. The volume lays particular emphasis on the reversal of trends in western and central Europe in the late sixteenth century, which was followed by a rapid increase in Jewish numbers and activity, and far-reaching reorganization of Jewish society and institutions. A major consequence of these changes was a much expanded and more varied Jewish role in European civilization as a whole. The first edition of this book was the joint winner of the Wolfson Literary Prize for History in 1986. For this third edition, the text has been updated and includes a new introduction.